The relationship between the PD-1/PD-L1 pathway and DNA mismatch repair in cervical cancer and its clinical significance - Feng YC; Ji WL; Yue N; Huang YC; Ma XM (Cancer Management and Research, 2018)
Yang-chun Feng,1,2 Wen-li Ji,3 Na Yue,3 Yan-chun Huang,2 Xiu-min Ma1 1Clinical Laboratory Center, The First Affiliated Hospital of Xinjiang Medical University, 2Clinical Laboratory Center, 3Clinical Pathology Center, Tumor Hospital Affiliated to Xinjiang Medical University, Urumqi, People’s Republic of China Background: According to recent clinical observations, deficient DNA mismatch repair (dMMR) is capable of improving antitumor effects of the PD-1/PD-L1 pathway, suggesting that dMMR may act as a prognostic indicator of PD-1/PD-L1 antibody drugs. In this study, we examined the dMMR and PD-1/PD-L1 expression, as well as explored the correlation of dMMR status with PD-1/PD-L1 expression in cervical cancer patients, in order to optimize cervical cancer patient selection for PD-1/PD-L1 antibody drug treatment, which is helpful to avoid adverse effects and keep costs manageable. Methods: Sixty-six tissue samples from patients with squamous cell carcinoma were collected, and data of their clinical characteristics were also gathered. Based on these samples, the expression levels of MLH1, MSH2, and PD-L1 in cancer cells were tested by immunohistochemical assay (IHC). Moreover, PD-1/PD-L1 expression in tumor-invading lymphocytes (TILs) was detected by IHC as well. Six single-nucleotide-repeat markers of microsatellite instability (MSI), including NR-27, MONO-27, BAT-25, NR-24, NR-21, and BAT-26, were tested by capillary electrophoresis sequencer analysis. According to expression of MLH1, MSH2 and the MSI test, all 66 cases were divided into dMMR or proficient DNA mismatch repair (pMMR) groups. The comparisons of dMMR and PD-L1 in cancer cells and of PD-1/PD-L1 in TILs were conducted categorized by age, childbearing history, history of abortion, ethnicity, and cancer cell differentiation subgroup. Furthermore, PD-L1 levels in cancer cells and PD-1/PD-L1 in TILs were analyzed and compared in both dMMR and pMMR subgroups. Results: Of the patient samples, 25.8% were associated with dMMR. PD-L1 in cancer cells, PD-L1 in TILs, and PD-1 in TILs took up 59.1%, 47.0%, and 60.6%, respectively. The data indicated that both dMMR and PD-L1 overexpression resulted from lower cancer differentiation, more incidences of childbearing, and a history of abortion. Abortion could significantly increase PD-1 expression levels in TILs. Additionally, more incidence of childbearing or older age (35–55 years) was able to upregulate PD-L1 expression in TILs. Statistical difference of PD-L1 in cancer cells could be observed between dMMR and pMMR subgroups. In the dMMR group, PD-L1 in cancer cells and PD-1 in TILs had no correlation (rs=0.161, p=0.537), but in the pMMR group, they had good correlation (rs=0.645, p<0.001). Conclusion: According to prior studies and our own experiments, PD-L1 in both cancer cells and TILs and PD-1 in TILs are widely observed in cervical cancer patients, indicating that there may be potential to apply PD-1/PD-L1 antibody drugs in cervical cancer. dMMR patients are associated with higher PD-L1 expression compared with pMMR ones, which suggested that PD-1/PD-L1 antibody drugs may work well in dMMR cervical cancer patients. Moreover, in patients with more incidences of childbearing or abortion, dMMR may be a molecular detection target for clinical application of PD-1/PD-L1 antibody drugs. Keywords: programmed cell death 1, programmed cell death 1 ligand 1, DNA mismatch repair system, cervical cancer